PERSEPSI MASYARAKAT TERHADAP ISU PAJAK LINGKUNGAN DI KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO (SITARO) - CELLINIA TUTER (Jurnal Ekonomi dan Bisnis Airlangga, 2020)
This study aims to enrich the literature on public policy, especially tax policy environment is important to protect the natural kseimbangan and to contribute to the government about how this environmental tax policy should be implemented in the future with regard to the interests of local communities are far remote.This study used a qualitative approach to the sources of data used are primary data in the form of interviews with stakeholders, such as governments, small businesses, and the general public and secondary data such as library materials, such as laws and regulations on environmental taxes. Objects in this study is Sitaro Islands Regency (Sitaro).The results of this study indicate that the level of awareness of the various parties in Sitaro Islands District is still lacking; There are three areas that must be considered government in formulating tax policy environment that is the process of establishing an environmental tax policy, the imposition of environmental tax rate basis and management of environmental taxes; Environmental taxes can serve as regulatory functions and functions budgetair; Public perceptions of the environmental tax is the first goal for the interest in protecting the environment from pollution and the second is to increase government revenue; The local government is considered more appropriate in determining the environmental tax policy than the central government since the area is more aware of the conditions of their respective regions; Environmental taxes can be applied as long as proportionally; Sitaro Islands District which is a remote area already requires an environmental tax for air pollution that is currently underway and is used to protect the local ecosystem.